Application of metadata modeling to dispute review report management - Zhu, Yimin; Bayraktar, Mehmet Emre; Chen, Shu-Ching (Journal of Civil Engineering and Management, 2010)
Disagreements in construction projects often result in litigation that is both time‐consuming and expensive. A dispute review board (DRB) provides a valuable and proven alternative method of dispute resolution. Currently, the Florida Department of Transportation (FDOT) stores DRB reports in portable document format (PDF) with limited search capability. Improving information retrieval of DRB documents and providing a certain level of integration of DRB reports with relevant but heterogeneous data and documents is the key to enhancing the current FDOT DRB system. This paper presents a web‐based data management framework to improve information management processes of the FDOT DRB system by providing key features such as metadata generation, an integrated review process, a simple issue description, member information management, and versatile information search. The new system not only allows DRB members and FDOT construction engineers to store and retrieve DRB reports but also provides more functionality to process those re‐ports. New functionalities include a structured search based on the metadata of DRB reports, an unstructured search using advanced computer technology, and the integration of DRB reports with other related information for analysis. This type of functionality improves the efficiency and effectiveness of the DRB system.First Published Online: 10 Feb 2011